Educational Intervention on Self Efficacy among Postoperative Fracture: A Literature Review - Sri Wirayuni Ni Luh Putu; Sri Yona (International Journal of Nursing and Health Services (IJNHS), 2021)
Fracture is a disruption of the normal discontinuity of bone and causes the surrounding tissue to be disrupted. Management of fractures is generally divided into recognition, reduction, retention, and rehabilitation. Exercises in the postoperative fracture patient rehabilitation program require patience and take a long time to achieve maximum cure. Nurses' therapeutic action in helping patients do rehabilitation exercises is by increasing the patient's self-efficacy to be independent in carrying out activities. Efforts to increase self-efficacy can be made through nursing interventions. This literature review aimed to explore the appropriate interventions on improving self-efficacy among postoperative fracture patients. Methods: This study was obtained from 4 databases, namely EBSCO, Key clinical, Willey, and Proquest, using inclusion and exclusion criteria. Results obtained. Decreased self-efficacy can occur in cases that require long action both for the healing process and chronic disease and when taking actions to maintain health, including post-surgery fractures. In conclusion, educational media will make it easier to provide interventions in increasing self-efficacy by paying attention to the factors that affect self-efficacy, namely master experience, vicarious experience, verbal persuasion, and emotional Arousal. The recommendation is that patients need support for adjusting the use of tools in providing education, providing logistics from samples in the application of education through technology media and to parents